The role of foreign direct investment in achieving economic growth - China case study - mansour, abdennour (Journal of Research in Finance and Accounting, 2023)
China achieved great economic growth, Making it currently one of the strongest economies in the world; due to economic openness to the world. foreign direct investment was an essential element. In our study, we concluded that China's openness to foreign direct investment had a positive impact on the rise in economic growth. This is evident in China's acquisition of modern manufacturing technology; the rise of its exports ; The significant growth in gross domestic product.